Trade, real exchange rate, and growth - Casares, Enrique (Estudios de Economía, 2016)
We develop an endogenous growth model with three goods, exportable, importableand non-tradable. We study the response of the real exchange rate and ofthe economy growth rate to a decrease in the tariff rate. We show that tradeliberalization must be followed by a depreciation of the real exchange rate. Wededuce that the growth rate of the economy increases in the long run. We affirmthat the Mexican economy did not follow this behavior in the period after thetrade liberalization, so the result was a deficient economic growth.